Gambaran Tingkat Daya Ingat Berdasarkan Tes IST pada Mahasiswa Psikologi Universitas Potensi Utama Medan - Fenty Zahara Nasution; Nadia Syafira (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
One of the tests that measures intelligence is the IST Test with 9 sub tests, and one of the sub tests in it is the last sub test, namely ME (Merkaufgaben). This subtest measures memory. This memory is closely related to attention and the ability to remember. Memory can be said to be sharp or dull when viewed from the accuracy, thoroughness or outline, or shallowness of the memory content. Estimates, feelings, emotions, affection, hopes and desires; Also plays a role in memory function. In this research, the researcher took only one thing, namely memory ability, the sample was carried out on psychology students in semesters 4, 6, 8, totaling 98 students. Using descriptive research methods. The aim of this research is to see a picture of the memory level of Psychology students at the Main Potential University in the morning and evening students because memory is very important for their ongoing learning process. Recall or memory is a mental process that an individual has to code, store, maintain and remember information, knowledge or past experiences in the brain which can be recalled for use some time later. This research approach uses a 6 minute test, then scoring based on morning and evening groups and based on semester level. Tests are given based on each class, the morning class is carried out during the morning class at 09.00 and the evening class is carried out at 18.00. The results obtained were that the superior level of memory was found in semester 8 students at 17.3%, semester 6 at 11.2%, semester 4 at 7.14%. High average memory level at semester 8 at 13.26% and semester 6 at 9.1% and semester 4 at 13.26%. 7 is 7.14% Average memory level is located in semester 6 with 14, namely 14.26% and semester 4 with 10, namely 10.20% and semester 8, namely 3, is 3.06%. Low Average level of memory is located in semester 6, namely 7, namely 7.14% and semester 6. of 6, namely 1.12% and semester 8 of 1 with 1.02%. The highest level of superior memory based on morning and evening classes is in semester 8 of the evening class, 17.34%. These results are useful in the future and need to be improved in upgrading memory to be able to carry out daily learning activities.